2012
DOI: 10.1152/japplphysiol.00800.2012
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological model of muscle fatigue and the power-endurance relationship

Abstract: The relationship between power output and the time that it can be sustained during exercise (i.e., endurance) at high intensities is curvilinear. Although fatigue is implicit in this relationship, there is little evidence pertaining to it. To address this, we developed a phenomenological model that predicts the temporal response of muscle power during submaximal and maximal exercise and which was based on the type, contractile properties (e.g., fatiguability), and recruitment of motor units (MUs) during exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Subtle variations in motor unit recruitment, metabolism, and blood flow within trials, or between days, may result in the system being tripped into the severe domain when it would be expected to be in the heavy domain and vice versa. Indeed, James and Green ( 39 ) produced realistic power–duration curves during constant load and all-out exercise by modeling the effect of fatigue on the motor unit pool. The importance of this is that the aforementioned heterogeneities could increase the probability of motor units developing functionally significant levels of fatigue, leading to the recruitment of additional, and even less fatigue-resistant motor units.…”
Section: Discussionmentioning
confidence: 99%
“…Subtle variations in motor unit recruitment, metabolism, and blood flow within trials, or between days, may result in the system being tripped into the severe domain when it would be expected to be in the heavy domain and vice versa. Indeed, James and Green ( 39 ) produced realistic power–duration curves during constant load and all-out exercise by modeling the effect of fatigue on the motor unit pool. The importance of this is that the aforementioned heterogeneities could increase the probability of motor units developing functionally significant levels of fatigue, leading to the recruitment of additional, and even less fatigue-resistant motor units.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, dynamic contractions are more relevant to typical occupational demands, and MFMs would have more potential for practical use if they were applicable for such efforts. Indeed, recent authors of models applicable to dynamic tasks (James and Green, 2012;Marion et al, 2010;Sih et al, 2012;Ma et al, 2012) acknowledge this need, in part due to the failure of older models in predicting muscle fatigue in diverse conditions. Meanwhile, ergonomics approaches and tools are typically more focused on 'higher-level' aspects of biomechanical systems (e.g., muscle physical capacity), and for practical application they need to avoid excessive complexities (e.g., of physiological mechanisms).…”
Section: Discussionmentioning
confidence: 99%
“…The curvilinear effects of intensity on fatigue and endurance are accentuated by increasing the proportion of type II muscle fibres (James and Green 2012), suggesting that any effect of fibre type on fatigue is more apparent at higher intensities. For the gastrocnemius lateralis muscle, the cross-sectional area occupied by type II muscle fibres is greater in younger than older subjects for both sexes (Coggan et al 1992).…”
Section: Mechanismsmentioning
confidence: 99%
“…The well-established relationship between intensity and endurance implies that fatigue is a curvilinear function of intensity (James and Green 2012), but there is limited empirical evidence about the intensity-fatigue relationship. In a study of young males, rates of fatigue were assessed at seven intensities of calf exercise between 30 and 90 %MVC (Egana and Green 2007) and the findings suggested that fatigue was a curvilinear function of intensity.…”
Section: Intensity and Fatiguementioning
confidence: 99%